1996
DOI: 10.1088/0268-1242/11/7/025
|View full text |Cite
|
Sign up to set email alerts
|

Au - Be/Ru/Au multilayer metallization as a stable ohmic contact scheme to p-type InP

Abstract: An attempt has been made to improve the electrical and metallurgical stability of Au-Be alloyed contacts to moderately doped p-type InP by minimizing the thickness of the Au-Be contact layer and using an Ru layer as a new, more effective diffusion barrier between the Au-Be and a thick Au top layer. It was found that the Au-Be contact layer only 40-50 nm thick is sufficient to give excellent ohmic contacts with specific contact resistance values as low as 2 × 10 −8 and 7 × 10 −8 m 2 (for N A -N D = (3-4) × 10 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The obtained minimum resistivity values conform to the moderate doping level of the InGaP epitaxial layers ( p % 2 Â 10 18 cm --3 ) and in spite of the larger bandgap ($1.9 eV) of InGaP, they are fully comparable to those for alloyed Au(Be, Zn) [5,18] and non-alloyed Ge/Pd(Zn) [14,15] Ohmic contacts to p-type InP with similar doping concentration.…”
Section: Electrical Propertiessupporting
confidence: 70%
See 1 more Smart Citation
“…The obtained minimum resistivity values conform to the moderate doping level of the InGaP epitaxial layers ( p % 2 Â 10 18 cm --3 ) and in spite of the larger bandgap ($1.9 eV) of InGaP, they are fully comparable to those for alloyed Au(Be, Zn) [5,18] and non-alloyed Ge/Pd(Zn) [14,15] Ohmic contacts to p-type InP with similar doping concentration.…”
Section: Electrical Propertiessupporting
confidence: 70%
“…Although Au-based contacts to InP and related compounds yield satisfactory contact resistivities, some problems (such as nonuniform surface and spiking interface and deep migration of Au into semiconductor) can arise at higher temperatures, which can cause device degradation and/or early failure [3]. To minimize the undesirable interfacial reactions and the migration of Au, various technological measures have been proposed [4][5][6]. Most of the effort, however, has been devoted to the development of low-resistance, shallow, non-Au-based Ohmic contacts, particularly those where the Au contact layer is replaced by Pd.…”
Section: Introductionmentioning
confidence: 99%
“…Because V and Ti might readily react with Au, we inserted a Pt or Ru layer beneath the Au capping layer. Platinum is often used to suppress Au indiffusion in other contacts, and Ru is a good diffusion barrier for Au, as shown by Malina et al 8 However, as shown in Table I, high specific contact resistances from mid-10 −6 to mid-10 −5 ⍀ cm 2 were observed for the as-deposited V/Pt/Au ͑40:40:80 nm͒, Ti/Pt/Au ͑40:50:80 nm͒, and Ru/V/Ru/Au ͑2:40:20:80 nm͒ contacts. Therefore, contacts with Ni, Pt, and Pd layers deposited directly on the semiconductor were next tested.…”
Section: Resultsmentioning
confidence: 99%
“…8(j), Malina et al 57 obtained extremely low contact resistivities for p-InP. Here, 57 Au-Be was used for contacting the semiconductor and q c ¼ 2 Â 10 À8 X cm 2 was obtained after annealing, for a carrier concentration of (3-4) Â 10 18 cm À3 . The low q c could be a result of increased carrier concentration at the interface due to Be dopant diffusion in InP.…”
Section: A Effect Of Non-parabolicity Metal Fermi Energy and Carrimentioning
confidence: 94%